Evaluation report on I.R.D. including E.R.R.P. Programme in Balangir District, 1989 (Planning & Co-ordination Dept., 1989)
Assessment of the Integrated Rural Development Programme and Economic Rehabilitation of the Rural Poor Programme in Balangir District of Orissa, India.